Pengaruh bursa saham Regional Asia Tenggara 5, Tiongkok dan USA terhadap IHSG : Perbandingan periode sebelum dan selama shock perekonomian global - Nugraha, Handy; Putriani, Santi; Putriana, Sinta (Nur Science Institute, 2023)
The 2018–2022 period is one of global economic uncertainty due to the US trade war with China and the economic recession due to the COVID-19 pandemic. These factors put pressure on the financial sector and influence investment behavior. This research aims to determine the influence of five regional stock exchanges in Southeast Asia, China, and the USA, domestic interest rates, and inflation on the IHSG, then compare the periods during the COVID-19 pandemic shock. The research method uses the Vector Error Correction Model (VECM). The analysis results show that the Southeast Asia regional stock exchange has a significant influence in the long term but no influence in the short term. An interesting finding in this research is that several stock exchange variables and domestic interest rates had different influences before and during the shock of the COVID-19 pandemic.